Biblia w kulturze zachodniej: słabość, kamuflaż i strategie przetrwania - Rychter, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2007)
Ewa Rychter The Bible in Western Culture: Weakness, Camouflage and Survival Strategies The article is a reflection on the ways in which Gianni Vattimo and Jonathan Sheehan on the one hand, and Hugh Pyper and Herbert Schneidau on the other hand, perceive the relationship between the Bible and Western culture. I demonstrate that for all of those thinkers the biblical text tunes in to the contemporary cultural context remarkably well. I also argue, however, that unlike Vattimo, Pyper and Schneidau — two contemporary biblical scholars — maintain that the weak status of the Bible should not be taken for granted. Pyper and Schneidau suggest that since the Scripture's weakness may be a survival strategy (a camouflage), one should leave open the possibility that the Bible's cultural stance could undergo a surprising transformation in the future.